Covid-19 and the Colombian cattle sector: Current and potential developments, impacts and mitigation options - Burkart, Stefan; Díaz, Manuel Francisco; Enciso, Karen; Urrea Benítez, José Luis; Charry, Andrés; Triana Ángel, Natalia (Bioversity International and the International Center for Tropical Agriculture, 2021)
The COVID-19 pandemic is affecting the Colombian cattle sector. First impacts and short-term mitigation measures are already visible in all links of the beef and dairy value chains. The full magnitude of the crisis is not yet clear but most impacts already are or will be negative and will affect the beef and dairy value chain’s performance in the near future. However, some positive trends are also occurring and could, at least to some extent, endure the crisis and help building a more resilient food system for the future. The objective of this study is to shed light on the current and potential developments, impacts and mitigation options of the COVID-19 pandemic on the Colombian cattle sector. Through literature, media and legal document review, we provide a thorough analysis for the different beef and dairy value chain links and framework conditions, and also include a perspective of how the pandemic affects more vulnerable parts of the population, rural education and on-going efforts towards sustainable intensification of the cattle sector. Our results show that consumer preferences will change towards more food safety, traceability, animal welfare and sustainability and the sector will need to understand this and push value chain formalisation and consumer communication. The transformation of the primary sector towards more sustainability and efficiency is becoming urgent, not only to increase resilience during times of crisis (as in the actual COVID-19 situation), but also to face the aggravating effects of climate change and combat inequality. Digitalisation and virtualisation have become important means during the crisis in all links of the value chains, creating opportunities for sustainably increasing sector efficiency. Research can play a fundamental role in analysing and understanding the impacts posed by the current crisis, providing technologies and recommendations for recovery, and developing solutions for building resilient food systems. Our results serve as guide for policy- and decision-makers to help understanding potential impacts of the pandemic and for the development of adequate mitigation measures in order to prepare the sector better for future crises.